Growth deregulation and interaction with host hemocytes contribute to tumor progression in a Drosophila brain tumor model. - Voutyraki, C.; Choromidis, A.; Meligkounaki, A.; Vlachopoulos, N.A.; Theodorou, V.; Grammenoudi, S.; Athanasiadis, E.; Monticelli, S.; Giangrande, A.; Delidakis, C.; Zacharioudaki, E. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Tumors constantly interact with their microenvironment. Here, we present data on a Notch-induced neural stem cell (NSC) tumor in Drosophila, which can be immortalized by serial transplantation in adult hosts. This tumor arises in the larva by virtue of the ability of Notch to suppress early differentiation-promoting factors in NSC progeny. Guided by transcriptome data, we have addressed both tumor-intrinsic and microenvironment-specific factors and how they contribute to tumor growth and host demise. The growth promoting factors Myc, Imp, and Insulin receptor in the tumor cells are important for tumor expansion and killing of the host. From the host's side, hemocytes, professional phagocytic blood cells, are found associated with tumor cells. Phagocytic receptors, like NimC1, are needed in hemocytes to enable them to capture and engulf tumor cells, restricting their growth. In addition to their protective role, hemocytes may also increase the host's morbidity by their propensity to produce damaging extracellular reactive oxygen species.